Glycosylated Hemoglobin Levels and Lipid Profile in Type 1 Diabetes Mellitus and Precipitating Factorsin Diabetic Ketoacidosis - Chilumula Monica; Saleem (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Type-1 Diabetes Mellitus is the most common endocrine-metabolic disorder of childhood and adolescence. The diseases has a prevalence of approximately 1 in 2500 children at age 5 years to approximately 1 in 300 children by age 18 years. A recent study from Madras suggests that diabetes in Indian children is present in a frequency of 10.5 per 1,00,000 patient years. Prevalence of childhood diabetes among urban population in India is 0.26 per 1000. Type-1 diabetes constituted nearly 90 to 100% of all children with diabetes. Objective: The objectives of this research were to study the levels of glycosylated hemoglobin and lipid profile in type 1 diabetes mellitus in children attending Gandhi Hospital Secunderabad, Telangana and to study the precipitating factors in Diabetic Ketoacidosis (DKA). Subjects and Methods:Design: This was a Cross-Sectional study. Duration: One year and six months i.e. from January 2017 to June 2018. Participants: 50 diabetic children of age less than 18 years attending Gandhi Hospital, Secunderabad, Telangana were included in the study.The diabetic cases were studied using a predesigned and pretested proforma. A detailed clinical examination was carried out with detailed anthropometric measurements and necessary lab investigations were done. Metabolic profile was assessed by investigating for blood sugar levels, glycosylated hemoglobin, and lipid profile. Rates, ratios and percentages of presentations and significance were calculated using Chi-square test.Result:48 % cases had onset of diabetes Mellitus at 13-18 years with Male: female ratio of 1.27: 1. 20 % had family history of diabetes. 16 % children had normal nutrition, 20 % children had grade I and grade II, 38% had grade III and 6 % children had grade IV. 54% children had glycosylated hemoglobin level of more than 10% indicating poor glycemic control, 32 % had fair control, and 14 % had good glycosylated hemoglobin levels. 62 % presented with fever , 40 % presented with symptoms of polyuria, polydipsia and polyphagia, 37.5 % presented with vomiting, 18 % children with loose stools, abdominal pain, 20 % children had breathlessness, 6% presented with seizures. 88.9% were diagnosed to have diabetic ketoacidosis as their initial presentation of diabetes mellitus Causes for precipitating factors of diabetic ketoacidosis were associated infections like pneumonia (22 %) and urinary tract infection(16 %), Non availability of insulin doses (25%), non-acceptance by child (16.66 %). Recurrent hospitalization in the patients with 5 years diabetic duration was statistically significant. Common causes being hypoglycemia (38 %) recurrent DKA (24 %), pneumonia (12 %) and urinary tract infections (8 %). 23.52% cases were non-compliant.Conclusion:More than half of the cases(54%) had poor glycemic control. Majority presented with classical symptoms of polyuria, polydipsia, polyphagia, fever, breathlessness and diabetic ketoacidosis as clinical presentation. Causes for precipitating factors of diabetic ketoacidosis were associated infections like pneumonia and urinary tract infection, non-availability of insulin doses and non- acceptance by child.